Continuous Regional Arterial Infusion of Protease Inhibitors Has No Efficacy in the Treatment of Severe Acute Pancreatitis: A Retrospective Multicenter Cohort Study. Issue 4 (April 2017) - Horibe, Masayasu; Sasaki, Mitsuhito; Sanui, Masamitsu; Sugiyama, Daisuke; Iwasaki, Eisuke; Yamagishi, Yoshiyuki; Sawano, Hirotaka; Goto, Takashi; Ikeura, Tsukasa; Hamada, Tsuyoshi; Oda, Takuya; Yasuda, Hideto; et al.
Abstract : Objective: The aim of this study is to assess the effectiveness of continuous regional arterial infusion (CRAI) of protease inhibitors in patients with severe acute pancreatitis (SAP) including acute necrotizing pancreatitis. Methods: This retrospective study was conducted among 44 institutions in Japan from 2009 to 2013. Patients 18 years or older diagnosed with SAP according to the criteria of the Japanese Ministry of Health, Labour and Welfare study group (2008) were consecutively enrolled. We evaluated the association between CRAI of protease inhibitors and mortality, incidence of infection, and the need for surgical intervention using multivariable logistic regression analysis. Results: Of 1159 patients admitted, 1097 patients with all required data were included for analysis. Three hundred and seventy-four (34.1%) patients underwent CRAI of protease inhibitors and 723 (65.9%) did not. In multivariable analysis, CRAI of protease inhibitors was not associated with a reduction in mortality, infection rate, or need for surgical intervention (odds ratio [OR] 0.79, 95% confidence interval [CI] 0.47–1.32, P = 0.36; OR 0.97, 95% CI 0.61–1.54, P = 0.89; OR 0.76, 95% CI 0.50–1.15, P = 0.19; respectively). Conclusions: Continuous regional arterial infusion of protease inhibitors was not efficacious in the treatment of patients with SAP.